Rhenium and technetium-complexed silicon rhodamines as near-infrared imaging probes for bimodal SPECT- and optical imaging - Kanagasundaram, Thines; Kramer, Carsten Sven; Boros, Eszter; Kopka, Klaus (Dalton transactions, 2020)
Fluorescent Si-rhodamines were modified to enable complexation with the Re(i)- and 99mTc(i)-tricarbonyl core. The corresponding complexes exhibit suitable properties as bimodal imaging probes for SPECT- and optical imaging in vitro. Importantly, the novel in- aqueous-solution-stable, functionalized Si-rhodamines retain favourable optical properties after complexation (QY = 0.09, λabs = 654 nm, λem = 669 nm in PBS) and show promising near-infrared optical properties for potential in vivo applications enabling bimodal scintigraphic imaging and optical imaging, e.g. used in radio- and fluorescence-guided tumour resection.